1997
DOI: 10.1093/ajcn/66.3.557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strength or aerobic training on body composition, resting metabolic rate, and peak oxygen consumption in obese dieting subjects

Abstract: Given that resting metabolic rate (RMR) is related largely to the amount of fat-free mass (FFM), the hypothesis was that strength training, which stimulates muscle hypertrophy, would help preserve both FFM and RMR during dieting. In a randomized controlled intervention trial, moderately obese subjects (aged 19-48 y) were assigned to one of three groups: diet plus strength training, diet plus aerobic training, or diet only. Sixty-five subjects (25 men and 40 women) completed the study. They received a formula d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 38 publications
8
83
1
3
Order By: Relevance
“…However, these results are in agreement with other researchers [19,20] who have reported significant improvements in blood pressure among groups involved in increased physical activity and/or dietary interventions compared to control groups. For example, Wood and colleagues [20] found a significant reduction resting systolic and diastolic blood pressure in men and women in both D and DE compared to control groups after one year.…”
Section: Blood Pressure Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…However, these results are in agreement with other researchers [19,20] who have reported significant improvements in blood pressure among groups involved in increased physical activity and/or dietary interventions compared to control groups. For example, Wood and colleagues [20] found a significant reduction resting systolic and diastolic blood pressure in men and women in both D and DE compared to control groups after one year.…”
Section: Blood Pressure Measurementssupporting
confidence: 93%
“…Kraemer et al [14] have shown that the inclusion of both endurance and heavy resistance training three times per week resulted in a nearly complete preservation of LBM in a group of overweight men. Geliebter et al [19] have similarly shown that strength training significantly preserves LBM relative to either aerobic exercise or no exercise in diet-restricting obese subjects. Because our study was solely comprised of aerobic exercise, LBM was not as well preserved.…”
Section: Diet and Exercise On Body Compositionmentioning
confidence: 97%
“…In adults, weight training has been shown to be superior to aerobic exercise for the maintenance of fat-free mass during dietary restriction, [90][91][92] while aerobic and weight-training exercise in combination was found to be superior to either modality alone for decreasing whole body fat during dietary restriction. 90,93 Theoretically, a similar rationale for preserving fat-free mass would apply when selecting an optimal treatment for overweight in youth.…”
Section: Discussionmentioning
confidence: 99%
“…비만 치료를 위한 운동처방의 주된 목적은 체중감량 에 있지만, 실질적으로는 체지방량의 감소와 더불어 제 지방량의 유지 및 증가 또한 중요하다 [8][9][10]. 비만 환 자를 위해서는 적절한 에너지 소비와 상해 예방을 위해 운동 강도보다는 운동 시간을 증가시키는데 보다 중점 을 두는 것이 효과적이다.…”
Section: ) 운동요법unclassified